2020
DOI: 10.1097/hjh.0000000000002729
|View full text |Cite
|
Sign up to set email alerts
|

Uterine fibroids increase the risk of hypertensive disorders of pregnancy: a prospective cohort study

Abstract: Objective: It is unclear whether uterine fibroids are associated with the occurrence of hypertensive disorders of pregnancy (HDP). Thus, this study aimed to evaluate the association between uterine fibroids and HDP in a prospective cohort. Methods: Overall, 2404 pregnant women who received antenatal care were enrolled in a prospective cohort in China between 2014 and 2016; 2277 women met the inclusion criteria of this study. The clinical characteristics of participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…However, the association between uterine fibroids and PE has rarely been explored. Chen et al recently reported in a cohort study that uterine fibroids in early pregnancy were associated with an increased risk of hypertensive disorders of pregnancy ( 25 ). Our study, which specifically focused on PE as defined by ISSHP recommendations, reconfirmed this association and extended the generalization of the results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between uterine fibroids and PE has rarely been explored. Chen et al recently reported in a cohort study that uterine fibroids in early pregnancy were associated with an increased risk of hypertensive disorders of pregnancy ( 25 ). Our study, which specifically focused on PE as defined by ISSHP recommendations, reconfirmed this association and extended the generalization of the results.…”
Section: Discussionmentioning
confidence: 99%
“…37 Gynecological conditions, such as fibroids and PCOS, have been shown to be associated with a greater risk for adverse pregnancy outcomes, including preeclampsia. [39][40][41][42] While the gastrointestinal and gynecological systems are physically close, there is a lack of literature on how they interact. Our results may indicate that individually, gynecological conditions do not increase risk for preeclampsia, however their interaction with gastrointestinal conditions increases risk regardless of obesity.…”
Section: C1 Further Discussion Of Interaction Effectsmentioning
confidence: 99%
“…Some of these risk factors are age, race, body mass index, genetic, reproductive factors, sex hormones, obesity, lifestyle (diet, caffeine, alcohol use, physical activity, and stress), environmental factors and underlying diseases (hypertension and infection). [ 1 5 6 ]…”
Section: Introductionmentioning
confidence: 99%